Socialist People's Libyan Arab Jamahiriya : 2009 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Socialist People's Libyan Arab Jamahiriya. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Libya's macroeconomic performance in 2008 has been strong, with real GDP growth of about 4 percent, and record fiscal and external surpluses. The staff report for Libya's 2009 Article IV Consultation underlies economic developments and policies. The outlook has been adversely affected by the global crisis mostly through a decline in oil prices and output. This outlook is subject to downside risks relating to a further worsening in global economic conditions or a wavering of the efforts to improve the quality of public expenditure and advance structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet